Total factor productivity in dairy buffalo milk production in Nueva Ecija, Philippines - Sanchez, Zadieshar G. (Journal of Economics, Management & Agricultural Development, 2022)
This study analyzed the total factor productivity in dairy buffalo milk production in Nueva Ecija, Philippines. Specifically, it aimed to identify the factors that affect dairy buffalo milk production and analyze technical efficiency, scale efficiency, and technological change as sources of TFP growth. Panel data was established by gathering data from randomly selected dairy buffalo milk producers in Nueva Ecija for the years 2017 and 2020. The stochastic frontier analysis was applied to a Cobb-Douglas production function with an inefficiency effects model. It was found that the statistically significant factors of milk production were cows, forage areas, and dairy feeds. Cleaning frequency was the sole predictor that explained the variability among the respondents’ technical inefficiency. For the years covered, the computed TEC was zero, while scale efficiency change and technological progress were at (-0.52%) and 48.60%, respectively, making the total TFP change equal to 48.08%.